The Saint, Education and Ecofeminism: Analyzing the Empowerment and Development of Children and Women in the Zawiyya Ahansal Moroccco - Laudza'i Wafa, Mohamad (Parahyangan Center for International Studies, 2024)
Zawiyya as a place of teaching and spreading Islam in Morocco has had quite a significant influence. An Igurramen, or zawiya leader in the Berber tribe, is able to mobilize the population around him with his religious influence. Zawiyya Ahansal as a place of Islamic teaching in the Atlas Mountains has its own challenges as a marginalized area. The Igurramen collaborated with Cloe Medina Erickson to build the Atlas Cultural Foundationto develop and empower the people around the zawiyya, especially children and women, hence this action shows the collaborative care and awareness between the saint, educator, and ecofeminist. This article aims to provide an analysis of the conditions of children and women's development and empowerment in Zawiyya Ahansal, Morocco. Keywords: zawiyya, Ahansal, Morocco, ecofeminism